Peroxisome Proliferator-Activated Receptor Alpha Target Genes - Maryam Rakhshandehroo; Bianca Knoch; Michael Müller; Sander Kersten (PPAR Research)
The peroxisome proliferator-activated receptor alpha (PPARα) is a ligand-activated transcription factor involved in the regulation of a variety of processes, ranging from inflammation and immunity to nutrient metabolism and energy homeostasis. PPARα serves as a molecular target for hypolipidemic fibrates drugs which bind the receptor with high affinity. Furthermore, PPARα binds and is activated by numerous fatty acids and fatty acid-derived compounds. PPARα governs biological processes by altering the expression of a large number of target genes. Accordingly, the specific role of PPARα is directly related to the biological function of its target genes. Here, we present an overview of the involvement of PPARα in lipid metabolism and other pathways through a detailed analysis of the different known or putative PPARα target genes. The emphasis is on gene regulation by PPARα in liver although many of the results likely apply to other organs and tissues as well.